The effects of different voice qualities on the perceived personality of a speaker - Pearsell, Sara; Pape, Daniel (Frontiers in Communication, 2023)
Although previous studies investigated various aspects of voice quality perception and personality attribution there are no studies, to our knowledge, which simultaneously examine and compare the perception of various voice qualities when produced by the same individual. This work investigates how laryngeal and supralaryngeal voice quality variations of a speaker affect listeners’ perceived personality traits (and thus perceived charisma) of that same speaker. Six Canadian English speakers produced paragraphs varying the following voice qualities: modal, creaky, breathy (natural and artificial), (hyper-)nasalization, and smiling (natural and extreme). Listeners of a perception experiment were then tasked to rate ten statements for each presented audio stimulus. Statements were selected corresponding to a sub-section of the Big 5 personality traits shown to be linked to charisma perception. Results show significantly more positive listener ratings (i.e. higher ratings compared to modal) with medium effects sizes for both smiling variants across all personality traits. In contrast, creaky was perceived significantly more negatively overall for all personality traits, with a medium effect size. Nasal and breathy still achieved statistically significant rating differences compared to the modal baseline. However, the overall effect pattern was more complex, and effect sizes were small or negligible. Additionally, we found consistent differences for some voice qualities when examining listener ratings comparing male versus female speakers: for both creaky and smiling (but not for other voice qualities), female speakers were rated more negatively when producing creaky for some personality traits, whereas both smiling variants were consistently rated higher for females compared to males.